1967
DOI: 10.1111/j.1749-6632.1967.tb27683.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of T‐strains

Abstract: T-Strains have several characteristics in common with the genus Mycoplasma. Whether or not they are, in fact, mycoplasma has, on occasion, been questioned. One of the main criticisms has been the lack of electron-micrographs showing the morphology of these organisms.Two T-strains from the human genital tract, one from the bovine genital tract and one from the human oropharynx were examined by electron-microscopy. For this purpose, the strains were grown in medium without serum. It was not possible, however, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
1

Year Published

1969
1969
1991
1991

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…This study illustrates that U. diversum strain 2312 attaches to the outer surface of the bovine zona pellucida, that ureaplasmas do not penetrate the zona pellucida and that the organism does not cause morphological changes in bovine morulae following 16 hours incubation in vitro. The cellular morphology of U. diversum strain 2312 is identical to that described previously for U. urealyticum and U. diversum (24,25,26,27,28).…”
Section: Discussionsupporting
confidence: 73%
“…This study illustrates that U. diversum strain 2312 attaches to the outer surface of the bovine zona pellucida, that ureaplasmas do not penetrate the zona pellucida and that the organism does not cause morphological changes in bovine morulae following 16 hours incubation in vitro. The cellular morphology of U. diversum strain 2312 is identical to that described previously for U. urealyticum and U. diversum (24,25,26,27,28).…”
Section: Discussionsupporting
confidence: 73%
“…After solidification, small agar blocks (about 1 mm') with cells embedded were cut and fixed for 1 hr at room temperature (20-22 C) in 3% GA in VA buffer to which was added one part of YAP medium (yeast extract-sodium acetate-peptone medium [0.3%, 0.05%, and 0.3%, respectively; Difco products]) to ten parts of fixative (v/v). After this fixation, the agar blocks were rinsed twice with 0.2 M sucrose in VA buffer, pH 6.1, and stored overnight at 4 C. The blocks were then rinsed twice in pure VA buffer and then fixed ovemight (17) at room temperature (20)(21)(22) C) in 1% VA-buffered Os04 to which was added one part of YAP medium to ten parts of fixative. After a brief wash in VA buffer and a 1-hr treatment at 20 to 22 C with 2% uranylacetate in the same buffer, the agar blocks were dehydrated in 70%, 96%, and 100% alcohol, briefly treated with propylene oxide, and fialy embedded in Vestopal-W (18).…”
mentioning
confidence: 99%
“…Electron microscopy (EM) confirmed these observations and also showed that the cells divide primarily by budding in different directions, producing poly-directional growth ramifications (Shepard, 1969). The outer membrane is trilaminar with a surface layer of hair-like structures (Williams, 1967), and each coccus contains vacuoles and ribosomes, some of which may be arranged in geometrical patterns (Black, Birch-Andersen and Freundt, 1972).However, some more recent EM studies of thin sections and negatively stained preparations (Black et al, 1972) have described the organisms as short rods and filamentous forms with branches and terminal club-shaped swellings, rather than as spherical bodies embedded in a gelatinous matrix. In an attempt to resolve these differences we have examined the gross morphology and ultrastructure of five laboratory strains isolated from patients with nonspecific urethritis (NSU) (Furness, 1973), by several light-and electron-microscope techniques.…”
mentioning
confidence: 99%